Molecular epidemiology and mechanism of Klebsiella pneumoniae resistance to ertapenem but not to other carbapenems in China - Wang, Dongliang; Wang, Minggui; He, Tianpeng; Li, Dan; Zhang, Liqin; Zhang, Dongquan; Feng, Junshuai; Yang, Wenli; Yuan, Yuan (Frontiers in Microbiology, 2022)
Resistance to only ertapenem is an unusual phenotype of carbapenem-resistant Klebsiella pneumoniae (CRKP). This study aimed to investigate the molecular epidemiology and underlying mechanism involved in ertapenem resistance of K. pneumoniae strains that are susceptible to meropenem and imipenem. Among the 697 K. pneumoniae strains isolated from 11 grade A hospitals in China, 245 were CRKP strains, of which 18 strains resistant only to ertapenem were isolated. The genotypes, phenotypes, drug resistance homology, and drug sensitivity were analyzed; moreover, the expressions of efflux pump components and outer membrane proteins were assessed. The whole genomes of these 18 strains were sequenced and analyzed for mutations leading to drug resistance. The results revealed that ertapenem resistance may be related to ramR mutation. The function of ramR was confirmed using gene complementation to the original strain to determine the mechanism underlying ertapenem resistance of K. pneumoniae strains. In total, 7.4% of the tested CRKP strains were resistant only to ertapenem. None of these strains contained carbapenemase genes. Of the 18 ertapenem-resistant strains, 17 expressed the efflux pump, and outer membrane protein expression was reduced or absent in 4 strains. Whole-genome sequencing revealed the presence of mutations that introduced premature ramR codons stop in 14 strains (77.78%). When a functional copy of ramR was restored in the 14 strains, the minimum inhibitory concentration of ertapenem decreased, inhibition of efflux pumps was not detected, and the expression of outer membrane protein OmpK35 was either increased or was restored. These findings reveal the existence of ertapenem-resistant K. pneumoniae exhibiting no clonal transmission between strains. Mutations in ramR were demonstrated to cause outer membrane protein OmpK35 inhibition and over-expression of efflux pump in some strains, which is implicated in ertapenem resistance only in K. pneumoniae.